The Effect of Dividend per Share (DPS) and Earning per Share (EPS) on Share Prices in the Manufacturing Industry Listed on the IDX - Rizkia Maudy; Mukaram (Ebiz Prima Nusa, 2026)
Introduction: The study aims to examine the effect of Earning Per Share (EPS) and Dividend Per Share (DPS) on stock prices of manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The manufacturing sector was chosen due to its significant contribution to the economy, averaging 19% annually during this period. Although DPS increased from 114.6 (2020) to 130 (2022) and EPS rose from 175.15 (2020) to 191.6 (2022), stock prices remained volatile, raising questions about the consistency of these factors' influence. Methods: The research method uses a quantitative approach, with secondary data collected through purposive sampling from 40 companies over three years, yielding 120 samples. Panel data regression analysis with Fixed Effect Model using Eviews 12 produced the equation Yti = 2380.48656412 + 4.5170470461X1ti + 1.1370520741X2ti. Results: The results show that DPS has a significant effect on stock prices, while EPS does not significantly affect stock prices. However, the simultaneous test results indicate that DPS and EPS together influence stock prices. Conclusion and suggestion: It is recommended for companies to pay attention to dividend policies distributed to shareholders and for investors to consider DPS in investment decisions.